(untitled) - FREEMAN, M. HERBERT; HANNA, J. MARSHALL \ KAHN, GILBERT (USA, 1968)
1.The elements of accounting / 2.Business in the United States / 3.The Fundamental Elements of Accounting / 4.The Balance Sheet / 5.Analyzing Business Transactions / 6.Balance sheet transactions / 7.Financial Statements / 8.Using Accounts / 9.Accounts / 10.Recording Changes in Assets and Liabilities / 11.Recording Changes in Owner ' s Equity / 12.Journalizing and Posting / 13.The Journal / 14.The Ledger / 15.The Trial Balance and Financial Statements / 16.The Trial Balance / Financial Statements / 17.Closing The Ledger / 18.Closing Income and Expense Accounts / 19.Completing The Accounting Cycle / 20.Visualizing the Accounting Cycle / 21.Banking Activities / 22.Paying by Check / 23.Depositing Cash / 24.Reconciling the Bank Statement and the Checkbook / 25.Petty Cash
Incluye indice analitico pag.134
Keywords: CONTABILIDAD